Carbon monoxide and mitochondria-modulation of cell metabolism, redox response and cell death - Almeida, Ana S. (2015)
This work was supported by the Portuguese Fundacao para a Ciencia e Tecnologia (FCT) grant FCT-ANR/NEU-NMC/0022/2012, HLAV's FCT support IF/00185/2012 and Ana S. Almeida's SFRH/BD/78440/2011 fellowship.